Potentiometric method for determination of manganese additives for fuels - Захарчук, М.М.; Сидоренко, Н.О.; Ледовських, В.М. (Proceedings of National Aviation University (archive), 2008)
The article provides the results of research of using reduction-oxidizing potentiometric titration for determination of the manganese adds in the fuels, which are used in order to increase the octane number of fuels.